Arduino a technical reference : a handbook for technicians, engineers, and makers - Hughes, John M. (O'Reilly Media, Inc., 2016)
Rather than yet another project-based workbook, Arduino: A Technical Reference is a reference and handbook that thoroughly describes the electrical and performance aspects of an Arduino board and its software. This book brings together in one place all the information you need to get something done with Arduino. It will save you from endless web searches and digging through translations of datasheets or notes in project-based texts to find the information that corresponds to your own particular setup and question. Reference features include pinout diagrams, a discussion of the AVR microcontrollers used with Arduino boards, a look under the hood at the firmware and run-time libraries that make the Arduino unique, and extensive coverage of the various shields and add-on sensors that can be used with an Arduino. One chapter is devoted to creating a new shield from scratch. The book wraps up with detailed descriptions of three different projects: a programmable signal generator, a "smart" thermostat, and a programmable launch sequencer for model rockets. Each project highlights one or more topics that can be applied to other applications
Includes index. - Includes bibliographical references (pages 581-583) and index. - Print version record
Keywords: Arduino (Programmable controller); Arduino (Programmable controller) -- Programming; Microcontrollers -- Programming; Arduino (Automate programmable); Microcontrôleurs; Programmation; Arduino (Automate programmable); Programmation; TECHNOLOGY & ENGINEERING; Engineering (General); Microcontrollers; Programming